Analisis Pengaruh Peran Konsultan Manajemen Konstruksi terhadap Kinerja Pelaksanaan Proyek Tower Telekomunikasi - Duden Dodi Hartono (Syntax Literate, 2023)
The construction project consists of a series of interconnected activities throughout the project cycle, starting from planning (concept and feasibility studies), design (engineering and drafting), procurement, execution (construction), start-up and implementation, to operation and utilization. The purpose of this research is to analyze the influence of construction management consultant roles on the performance of telecommunication tower project implementation. This study utilizes a descriptive method, with the population comprising all employees of PT. Digjaya Mandiri Teknik, Mitratel, other construction management consultants, and contractors involved in telecommunication tower project implementation. The study involves a total of 50 experienced respondents who have worked for more than 4 years in telecommunication tower projects. The sample for this study includes employees engaged in telecommunication tower projects, both in the field and in the office. The findings of this research reinforce several previous theories and studies that discuss the influence of construction management consultant roles on project implementation performance. Based on the results and discussions in the previous chapter, the conclusion is drawn that there are factors that affect the improvement and decline in performance during the implementation of telecommunication tower projects, specifically related to the role of construction management consultants.